Higher education in the United Kingdom: A Handbook for students from overseas and their advisers - British council (London Britsh council-Longmans, 1966)
1966 Edition- issued every two years
Keywords: Education, Higher -- Great Britain -- Directories; Universities and colleges -- Great Britain -- Directories; Education, Higher